2022
DOI: 10.1186/s12879-022-07940-z
|View full text |Cite
|
Sign up to set email alerts
|

Time to trimethoprim/sulfamethoxazole initiation among patients with rheumatic disease complicated by Pneumocystis jirovecii pneumonia: impact on 90-day mortality

Abstract: Background Pneumocystis jirovecii pneumonia (PJP) is a life-threatening disease with increasing prevalence in patients with rheumatic disease. Trimethoprim/sulfamethoxazole (TMP/SMX) is an effective treatment for patients with rheumatic disease hospitalized for PJP. This study aimed to describe the 90-day mortality of patients with rheumatic disease complicated by PJP and investigate whether the administration of TMP/SMX after 7 days from initial symptoms correlates with 90-day mortality. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The second unexpected finding was that a non-negligible proportion of patients received the first dose of curative antibiotic treatment for PJP late: among patient not yet treated upon ICU admission, 12.7% received the first dose after the 96th hour. This is in line with what was reported years ago [11,24,[27][28][29], suggesting that the practices of intensivists may not have evolved since then. Despite a rich literature emphasizing the high index of suspicion of PJP when caring for immunocompromised patients with diffuse pneumonia, there still remains a considerable gap between theory and practice.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The second unexpected finding was that a non-negligible proportion of patients received the first dose of curative antibiotic treatment for PJP late: among patient not yet treated upon ICU admission, 12.7% received the first dose after the 96th hour. This is in line with what was reported years ago [11,24,[27][28][29], suggesting that the practices of intensivists may not have evolved since then. Despite a rich literature emphasizing the high index of suspicion of PJP when caring for immunocompromised patients with diffuse pneumonia, there still remains a considerable gap between theory and practice.…”
Section: Discussionsupporting
confidence: 91%
“…Our study further suggests that early treatment is of paramount importance, as it reveals that a delay of 4 days accelerated the time to death by a factor 6.75. This aligns with findings from earlier retrospective studies [24,28,29] and one prospective study, encompassing all PJP cases, whether requiring intensive care admission or not. That study demonstrated an increased risk of mortality of 1.11 for each day of delayed treatment [11].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Song et al. found that in patients with rheumatic disease and PCP, initiating treatment with TMP-SMX 7 days after the onset of symptoms was significantly linked to a higher 90-day mortality ( Song et al., 2022 ). These findings highlight the fact that delayed diagnosis and treatment are major contributors to increased mortality and the need for mechanical ventilation in PCP patients.…”
Section: Discussionmentioning
confidence: 99%